1994
DOI: 10.1063/1.357192
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy and giant magnetostriction of amorphous TbDyFe films

Abstract: The influence of internal stress on the magnetic anisotropy and the magnetostriction was investigated in sputter-deposited amorphous (Tb0.27Dy0.73)0.42Fe0.58 films. Films with tensile stress show in-plane anisotropy and giant magnetostriction of λ∥=400×10−6 at 1 T measured in a field parallel to the film plane at room temperature. The magnetostriction rises rapidly to λ∥=200×10−6 at 0.05 T and the coercivity is less than 0.01 T. On the other hand films with compressive stress show perpendicular anisotropy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 6 publications
3
53
0
Order By: Relevance
“…[10][11][12] The as-deposited films are always amorphous with relatively poor magnetic properties including magnetoelastic behavior. 13 The thin films must be crystallized to obtain mechanical and magnetic properties close to bulk Terfenol-D. This can be achieved either by depositing the film on a heated substrate or by post-annealing.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The as-deposited films are always amorphous with relatively poor magnetic properties including magnetoelastic behavior. 13 The thin films must be crystallized to obtain mechanical and magnetic properties close to bulk Terfenol-D. This can be achieved either by depositing the film on a heated substrate or by post-annealing.…”
Section: Introductionmentioning
confidence: 99%
“…4) The giant magnetostrictive films are affected by vacuum condition, chemical composition, microstructure, and internal stress. Among them, internal stress could dominate the magnetostrictive properties (Schatz et al, 1994, Xu et al, 2001). 13,14) Wada et al (1996) have reported that the magnetostrictive properties of Tb-Dy-Fe thin films prepared by ion beam sputtering system using Ar may be attributed to the internal stress induced by Ar inclusion during the deposition.…”
Section: Introductionmentioning
confidence: 99%
“…5 Additional reduction in anisotropy is possible by making the films amorphous, 6,7 however, this also causes a reduction in the saturation magnetostriction (λ ~ 10 -4 ). 1 A further decrease in switching field is possible by use of magnetic multilayers based on Kneller's exchange spring mechanism.…”
mentioning
confidence: 99%